Public Speaking for College & Career - Gregory, Hamilton (McGraw-Hill, 2010)
Prepare your students for public speaking with Hamilton Gregory’s Public Speaking for College and Career with free SpeechMate CD-ROM, sixth edition. With its wealth of student and work-oriented examples, this textbook teaches public speaking with a practical and accessible style